The Cambridge guide to women's writing in English - Sage, Lorna; Greer, Germaine 1939-; Showalter, Elaine (Gale virtual reference library, 1999)
An encyclopedia of women's writing in English, especially those writers and texts that have been popularly read in the last 25 years. Includes entries for writers, texts, general terms, genres and movements. Subjects range from early medieval English writing through today. Demonstrates the increase in literacy and the changes to the language as colonies evolved.